Immigration and Housing During Home Confinement: The Case of Sublet Rooms - Orozco-Martínez, Carolina; Bayona-i-Carrasco, Jordi; Gil Alonso, Fernando (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2022)
For the immigrant population sublet rooms are a common way of access to housing. In the context of the covid-19 juncture, this paper examines the impact of the mandatory home confinement decree at the beginning of the pandemic, on immigrants living in sublet rooms in the Barcelona Metropolitan Area. 27 semi-structured interviews carried out within this group are analyzed. The results show the worsening of pre-existing problems: coexistence problems, poor housing conditions, overcrowding or excessive prices, as well as the appearance of new difficulties due to constant and forced coexistence, not being able to use of public spaces and closure of institutions, affecting the physical and psychological health of this group. It is shown that subleasing, which hosts a large part of the residentially excluded population, does not guarantee a decent, adequate, and safe home to face home confinement.